P61 CORONARY ARTERY ECTASIA: AN ENEMY NOT TO BE UNDERESTIMATED IN ACUTE CORONARY SYNDROME. (18th May 2022) - Chietera, F; Ghetti, G
Abstract: Coronary artery ectasia is an abnormal dilatation of coronary arterial segment of at least 1.5 times that of a narrow normal coronary artery. Even if the overall incidence ranges between 4–9% of total angiography, it is correlated with poor outcome due to lower percutaneous procedural success, an higher incidence of no–reflow, distal embolization and stent thrombosis. We present two cases of high risk acute coronary syndrome patients with right coronary artery ectasia and different management in which intravascular ultrasound played a key role in determining interventional strategy. Case #1 : 55–year–old man presented with STEMI after VT–induced cardiac arrest treated with CPR and DC–shock with subsequent ROSC. Coronary angiography showed thrombotic occlusion in the middle tract of the right coronary artery treated with thrombus aspiration and subsequent PTCA + DES from the proximal to the distal tract of the severely ectatic artery with apparent good final angiographic result. However, at the IVUS control performed to verify the possible need for an additional stent in the context of flow turbulence, malapposition of the stent to the proximal–middle tract was highlighted with an important amount of probably thrombotic material between the stent and the vessel wall. Post dilation was therefore performed with NC balloons with IVUS documentation of resolution of the malapposition. Case #2: 59–year–old man hospitalized for NSTEMI. Coronary angiography showed severe left coronary ectasia in the absence of significant stenosis and subocclusive thrombus in the posterolateral branch of the right coronary artery with TIMI 2 flow in the context of diffuse CAE . A conservative strategy was undertaken with DAPT + LMWH due to the absence of symptoms and hemodynamic stability, as well as the associated high embolic risk. A follow–up coronary angiography was performed after one week of therapy with evidence of good recanalization of the branch (TIMI 3). IVUS control showed only minimal thrombotic component adhering to atherosclerotic plaque in the posterolateral branch with a MLA of 11.47 mm2 and a low percentage of stenosis (34.5%). A conservative strategy was therefore undertaken (DAPT 12 months). ACS management in patients with CAE is still challenging and a standardized approach is difficult to please. Strategies should be individualized based on clinical presentation and anatomic characteristics but coronary imaging should be routinely performed in this context.